Advances and caveats in modern achalasia management - Marcella Pesce; Rami Sweis (SAGE Publishing, 2021)
Achalasia is a rare esophageal motility disorder characterized by the incomplete relaxation of the lower esophageal sphincter (LES) and impaired peristaltic activity. The advent of high-resolution manometry (HRM) and the rapidly evolving role of therapeutic endoscopy have revolutionized the approach to the diagnosis and management of achalasia patients in the last decade. With advances in HRM technology and methodology, fluoroscopy and EndoFlip, achalasia can be differentiated into therapeutically meaningful phenotypes with a high degree of accuracy. Further, the newest treatment option, per-oral endoscopic myotomy (POEM), has become a staple therapy following the last 10 years of experience, and recent randomized trials appear to show no difference between POEM, graded pneumatic dilatation and surgical Heller myotomy in terms of short- and long-term efficacy or complication rate. On the other hand, how treatment outcomes are measured as well as the risk of reflux following therapy remain areas of contention. This review aims to summarize the recent advancements in achalasia testing and therapy, describes the recent randomized clinical trials as well as their potential setbacks, and touches on the future of personalizing achalasia treatment.